Exhaled breath condensate as a potential biomarker tool for idiopathic pulmonary fibrosis—a pilot study. (28th November 2017) - Rindlisbacher, Barbara; Strebel, Carina; Guler, Sabina; Kollár, Attila; Geiser, Thomas; Martin Fiedler, Georg; Benedikt Leichtle, Alexander; Bovet, Cédric; Funke-Chambour, Manuela
Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating lung disease with poor survival. There is an urgent need to better diagnose and monitor IPF patients as new treatments which slow down disease progression are now available. Exhaled breath condensate (EBC) is easily and non-invasively collected, but analysis of potential biomarkers is difficult due to low concentrations and methodological limitations. We used a non-targeted metabolomics approach to identify discriminatory metabolic profiles that distinguish IPF patients from healthy controls. For the pilot study set, we collected EBC from 10 stable IPF patients and 10 lung healthy controls. Samples were analyzed by ultra high-performance liquid chromatography coupled to high-resolution mass spectrometry in positive and negative ion mode. After data processing and statistical analysis, 58 metabolites were found to be discriminative between IPF patients and controls in the positive ion mode. One metabolite candidate m / z = 341.3514 at a retention time of 9.94 min was 2.5-fold up-regulated in IPF patients compared to healthy controls and validated in a second set of eight IPF patients and healthy controls. The identity of this metabolic feature still remains elusive. Our preliminary results identified a distinguished EBC profile of IPF patients compared to controls. Although these results need to be confirmed in additional individuals, EBC sampling for diagnosis and/or monitoring of IPF patients is a promising new method, which should be further explored. The EBC samples have been obtained within the clinical trial NCT02173145 at baseline.